Study of growth kinetic and modeling of ethanol production by Saccharomyces cerevisae - Ahmad, Farah; Jameel, Ahmed Tariq; Kamaruddin, Mohd Hider; Mel, Maizirwan (Academic Journals, 2011)
There is a growing interest in bioethanol as biofuel since it has the possibility to be the potential substitute for fossil fuels. Ethanol batch fermentation of Saccharomyces cerevisiae strain was carried out in 10 L stirred tank bioreactor for 72 h at 0.075 vvm of aeration and 75 rpm of agitation speed. 85.8% conversion efficiency of ethanol production from glucose substrate was accomplished. This study investigated the S. cerevisiae growth kinetics and ethanol productivity using computer simulation of four different kinetic models which are: Monod, Contois, Modified Monod and Teisser. Teisser model gave marginally better fit than other models tested as it obtained the highest correlation coefficient (0.96299). Based on Leudking-Piret model, it could be concluded that ethanol batch fermentation is a non-growth associated process.